Anatomy-Driven Medical Image Search - Simonyan, K.; Zisserman, A.; Criminisi, A.; Criminisi, Antonio (Radiological Society of North America (RSNA), 2010)
This paper presents an algorithm for content based medical image search, which allows querying by a specific region of interest. The user provides a bounding box for the region in a query image. The algorithm then retrieves images similar in content to the query with the region of interest detected and localized in each of them.